Kompetensi Guru Sekolah Dasar dalam Mmengajar Ilmu Pengetahuan Sosial(IPS) - Toha Mashudi (Ilmu Pendidikan: Jurnal Kajian Teori dan Praktik Kependidikan, 2002)
This study was designed to investigate the contribution of education level, frequency of participation in training, teaching experience, and attitudes toward teacher's profession to the elementary school teachers' competence in teaching Social Studies. The sample consisted of 160 elementary school teachers in Kedungkandang, Malang. Data were collected by using observation, questionnaire, and interview, and were analyzed statistically with multiple regression. This study revealed that the teachers' competence tended to be high. The contribution of teachers' participation in on-the-job training to the competence in teaching social studies was higher than the contribution of education level.